2012
DOI: 10.1002/acp.2856
|View full text |Cite
|
Sign up to set email alerts
|

Multisensory Assessment of Acoustic Comfort Aboard Metros: a Virtual Reality Study

Abstract: In this study, a multisensory methodology is used to assess acoustic comfort aboard different real-world metros by means of subjective annoyance and cognitive performance measures. Two experimental conditions were compared: unimodal versus bimodal. Immersive virtual reality was used to simulate journeys aboard metro coaches. Participants performed four tasks (Rey Test, Verbal Fluency, Backward Counting and Auditory Words Discrimination) while listening to metro sounds (unimodal condition) or while listening to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 59 publications
2
47
0
Order By: Relevance
“…Overall, it is important to point out that the results of this study are in line with the existing field studies and confirm that the innovative multisensory Immersive Virtual Reality methodology adopted here represents a suitable tool for the Environment Impact Assessment [30,37,38,39,40,41]. The proposed methodology seems to allow the investigation of the potential effects of the introduction of new infrastructure in an existing environment and to define in advance the better project choices that facilitate the preservation of both acoustic and visual quality of the environment [8,9,10,11,12,13].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Overall, it is important to point out that the results of this study are in line with the existing field studies and confirm that the innovative multisensory Immersive Virtual Reality methodology adopted here represents a suitable tool for the Environment Impact Assessment [30,37,38,39,40,41]. The proposed methodology seems to allow the investigation of the potential effects of the introduction of new infrastructure in an existing environment and to define in advance the better project choices that facilitate the preservation of both acoustic and visual quality of the environment [8,9,10,11,12,13].…”
Section: Discussionsupporting
confidence: 83%
“…Furthermore, the visual representation has been integrated with auralization systems that are meant to create audible sound files from numerical data, which can be simulated, measured or synthesised, obtaining convincing audio presentations. Maffei et al used the IVR system in different studies [39,40,41]. In a case-study of a new highway [41], it was found that conventional methods to assess noise impact based on noise maps and noise limits did not match even the real response of the population.…”
Section: Introductionmentioning
confidence: 99%
“…Acoustic comfort during metro journeys was assessed by [13] using IVR. The authors chose IVR for its ability to recreate similar visual and acoustic contexts while also providing an immersive and interactive experience.…”
Section: State-of-the-artmentioning
confidence: 99%
“…Transforming the Self into a Child, by Sánchez-Vives and Slater [72] where adults embodied in child bodies through VR change their perception regarding the size of environments and objects [73]. Other research related focus in approaches such as multisensory assessment [74], innovative audio visual approaches [75], noise perception in immersive environments [76] or multisensory immersive virtual environments [77].…”
Section: Virtual Reality and Its Approach To Simulationmentioning
confidence: 99%